A Handbook of a Kherep-Selket from the Tomb of Iufaa: The Book of Primeval Snakes - Landgráfová, Renata (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The Late Period shaft tombs at Abusir are located in the North-Western part of the Abusir necropolis and were built during a rather short span of time at the very end of 26 th Dynasty, between 530 and perhaps 525 BC. Among those, the tomb of Iufaa stands out by its size and by the extent of its interior decoration. Significant amount of the decorated space in Iufaa’s burial chamber were reserved for a series of texts and images that may be best denoted as a “Snake Encyclopedia”. The individual parts of this textual corpus cover the main parts of the arch of the western wall in the burial chamber of Iufaa. The opposite side of the burial chamber, the arch of the eastern wall, bears two texts (accompanied with images) that concern Underworld/divine snakes as well. Although this “encyclopedia” of Underworld serpentine beings still provides us with much more questions and puzzles than answers and insights, it also sheds a new light upon the religion, cult and afterlife beliefs of the Saite-Persian and Graeco-Roman Egypt. It witnesses the importance of giant snakes or primeval creatures in serpentine form that were believed to dwell in the Underworld and were directly linked to cosmogony and periodical renewal of the sun and of the world. As manifestations of Re and Osiris, the snakes become lords of life and death, hypostaseis of the cyclically rejuvenated Creator. The idea of renewal and rebirth is also closely connected with ritual purity and purification rites. Thus, the “Snake Encyclopedia” is accompanied by a corpus dedicated to the ritual cleansing of the pharaoh and of the deceased, which is represented textually and pictorially on the northern wall of Iufaa’s burial chamber and which features serpentine primordial beings as well. But the focus on not generally transmitted, pre-cosmological concepts is connected to yet another important aspect of the composition and other texts from Iufaa’s tomb, that have most probably served as a compendium of secret knowledge for the magicians of Selket. This motif helps us to interpret one of the main tasks of the composition in focus: it probably served to accumulate and transmit sacred knowledge and to use it to ensure that the deceased would be accepted into the blessed Afterlife.